Microstructural evolution, electrochemical and corrosion properties of AlxCoCrFeNiTiy high entropy alloys. (15th May 2019) - Qiu, Y.; Thomas, S.; Fabijanic, D.; Barlow, A.J.; Fraser, H.L.; Birbilis, N.
Abstract: The microstructure of the Al x CoCrFeNiTi y high entropy alloy (HEA) system was studied using X-ray diffraction, scanning and transmission electron microscopy. A microstructural evolution from single-phase FCC to FCC + BCC + B2 occurred with increasing Al content. The addition of a comparatively small amount of Ti led to the formation of a Fe-Cr sigma phase. The corrosion characteristics of the alloy system were studied across different compositions, with such an alloy system exhibiting a high resistance to general corrosion, superior to stainless steel 304L in 0.6 M NaCl. Cyclic potentiodynamic polarisation suggested that the HEAs studied underwent pitting corrosion following breakdown. From exposure testing, it was seen that very fine pitting, although not extensive in nature, was the principle form of corrosion for Al x CoCrFeNiTi y after prolonged immersion. There was little evidence of microgalvanic corrosion or selective dissolution of a particular phase observed, despite the heterogeneous microstructure and significant elemental segregation in the alloys studied. The composition of the surface films formed upon the Al x CoCrFeNiTi y alloys were elaborated by X-ray photoelectron spectroscopy, which provided new and further insights regarding the surface films of such alloys. The study herein contributes to an emerging understanding of the corrosion characteristics of high entropy alloys. Graphical abstract: Unlabelled Image Highlights: The microstructural evolution of Al x CoCrFeNiTi y CCAs is investigated in details using XRD, SEM and TEM. Good corrosion resistance of these CCAs in 0.6 M NaCl is revealed, with fine pitting as the main type of corrosion. The composition of the surface films was elaborated by XPS which provided new insights on the corrosion mechanisms of CCAs.